Verallgemeinerung des Wiman-Valironschen Satzes für ganze Funktionen mehrer komplexen Veränderlichen - Streliz, S. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ш. Стрелиц. Обобщение теоремы Вимана-Валирона для функции многих комплексных переменных Š. Strelicas. Vimano-Valirono teoremos apibendrinimas daugelio kintamųjų sveikosioms funkcijoms